Management practices of childhood malaria among caregivers in Ojo millitary cantonment, Lagos, nigeria: implication for child survival (2009)
The study explored home management practices for malaria by caregivers in the Military Cantonment, Ojo Lagos. Data was collected using pre-tested Focus Group Discussion guide and interviewer administered questionnaire. The 400 survey respondents were selected using the systematic sampling method while the discussion participants were purposively selected. Data analysis was done using EPI Info statistical software and thematic approaches. The mean age of respondents was 29 ±15.2 years while 89.8% of respondents were biological parents of the index children. High prevalence of malaria all year round caused by mosquitoes bite was indicated by 281(70.2%) respondents, while 73 (18.3%) of the respondents reported having lost a child under 5 years old to malaria related illnesses. Preventive practices were uncoordinated while awareness and use of ITNs is low. Home management practices of childhood malaria involved the immediate treatment with medicines available in the home. Sharing of left over drugs and herbs were common practices. Home treatment was preferred because of high costs 250(62.5%), unfriendly attitude of workers 195(48.8%) and long waiting time 194(48.5%) in the health facilities. Based on the findings there is the need to institute an awareness programme aimed at improving prompt home management of malaria in the barracks.